(untitled) (Dimensión Empresarial, 2015)
This research studied the efficiency of 44 hospitals Bolívar in 2010. The earlier through the application of DEA. calculated Technical Efficiencies Hospitals were using the DEA model focused on CCR-O outputs, the above through study of the financial statements of these hospitals. Of the 44 hospitals studied, 35 showed low efficiency, 1 had an average efficiency, 2 showed high efficiency and 6 hospitals were shown to be efficient, these were: That local saint Mary Hospital, Hospital San José That Local Achi, followed by That Health Center Cantagallo beds, That Hospital San Antonio de Padua, health center Giovani That Cristini, and finally the San Fernando That local hospital. With this research it was concluded that 13.64% of those tested had Hospitals optimum efficiency. The average efficiency of hospitals under investigation was 47.61%.